Analysis of the Role and Characteristics of Ceramic Resistors in Modern Electronics Applications - Hutagalung, Triono; Dicky Ahmad Fahrozy; Nasution, Risfan Akhari; Solly Aryza (International Journal of Economic, Technology and Social Sciences (Injects), 2023)
This research presents an in-depth analysis of the role and characteristics of ceramic resistors in the context of modern electronics applications. Ceramic resistors, as fundamental components in circuit design, play a critical role in controlling current and voltage, forming the basis for efficient and reliable circuit performanceThese advantages make ceramic resistors a reliable choice for applications that require high precision and reliability. Adjustable tolerances and high precision provide flexibility in selecting ceramic resistors according to the specific needs of an application. The diversity of sizes and powers enables the application of ceramic resistors in a variety of contexts, from consumer devices to high-power industrial and automotive systems. The importance of ceramic resistors is also reflected in their contribution to chip-film technology innovation. Its ability to adapt to the trend of miniaturization and component integration makes it relevant in the ever-evolving world of technology. With affordable production costs, ceramic resistors are an economical choice for mass production, supporting the development of widely affordable electronics technology. As a key element in the foundation of modern circuits, ceramic resistors play an irreplaceable role in advancing current and future electronics technology. The conclusions of this analysis provide deep insight into the contribution of ceramic resistors to the evolution of electronics technology and help guide the selection of appropriate components for specific applications.